Macrophage activation syndrome in systemic lupus erythematosus - a case report - Rogala, Maciej; Lorenc, Karol; Jabłońska, Klaudia; Kuc, Michał; Bielawska, Olga; Łoś, Tomasz; Giżewska, Kamila; Gulbicka, Marta (Journal of Education, Health and Sport, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening condition that results from the immune system hyperactivation. The primary form of HLH appears mainly in children and is caused by a genetically determined failure of NK and T cells. Secondary (acquired) HLH usually occurs due to insufficiency of these cells caused by other disease entities or drugs. Potential factors that may be responsible for the appearance of this rare condition include: malignancies (especially lymphomas), infections (EBV, CMV, HIV), autoimmune diseases (SLE, Still’s disease). The clinical appearance of hemophagocytic lymphohistiocytosis is dominated by persistent fever, hepatomegaly, splenomegaly, pallor of the skin, signs of hemorrhagic diathesis, lymph node enlargement. Characteristic abnormalities in laboratory tests include: hypertriglyceridemia, cytopenia, hyperferritinemia, hyperfibrinogenemia and hypertransaminasemia. One subtype of the secondary form of hemophagocytic lymphohistiocytosis, which is associated with rheumatic diseases, is called the macrophage activation syndrome (MAS). The following describes a case of a 26-year-old woman with exacerbated systemic lupus erythematosus, who was admitted to a Rheumatology Unit in severe general condition. Clinical presentation of the patient included primarily: long-lasting fever, hepatomegaly and splenomegaly. Various test were performed during her hospitalization, including laboratory test and a bone marrow biopsy. Finally, the woman was diagnosed with the macrophage activation syndrome. She was successfully treated with ciclosporin and methylprednisolone.